Searching for the "white crow": Stories of hockey, fishing and lessons learned chasing "bigfoot" from the perspectives of an academic greenhorn - Lyle Donald Hamm (Canadian Society for Studies in Education, 2017)
Adapted from a keynote address presented to Master's and Doctoral students in Atlantic Canada in 2014, the author recalls his own experiences as a graduate student in Alberta. In his message, he reflects on events and stories he heard, which brought balance to his life and motivated him to continue in his doctoral quest. Using the metaphor of "chasing Bigfoot" and Gaarder's (1996) "white crow," the author encourages graduate students to persist in their studies and grow resilience to overcome the challenges and barriers that are often present in academic graduate programs.